Doxycycline attenuates l-DOPA-induced dyskinesia through an anti-inflammatory effect in a hemiparkinsonian mouse model - dos Santos Pereira, Maurício; Nascimento, Glauce Crivelaro do; Bortolanza, Mariza; Michel, Patrick Pierre; Raisman-Vozari, Rita; Del Bel, Elaine (Frontiers in Pharmacology, 2022)
The pharmacological manipulation of neuroinflammation appears to be a promising strategy to alleviate L-DOPA-induced dyskinesia (LID) in Parkinson's disease (PD). Doxycycline (Doxy), a semisynthetic brain-penetrant tetracycline antibiotic having interesting anti-inflammatory properties, we addressed the possibility that this compound could resolve LID in L-DOPA-treated C57BL/6 mice presenting either moderate or intermediate lesions of the mesostriatal dopaminergic pathway generated by intrastriatal injections of 6-OHDA. Doxy, when given subcutaneously before L-DOPA at doses of 20 mg.kg-1 and 40 mg.kg-1, led to a significant LID reduction in mice with moderate and intermediate dopaminergic lesions, respectively. Importantly, Doxy did not reduce locomotor activity improved by L-DOPA. To address the molecular mechanism of Doxy, we sacrificed mice with mild lesions (i) to perform the immunodetection of tyrosine hydroxylase (TH) and Fos-B and (ii) to evaluate a panel of inflammation markers in the striatum, such as cyclooxygenase-2 and its downstream product Prostaglandin E2 along with the cytokines TNF-α, IL-1β and IL-6. TH-immunodetection revealed that vehicle and Doxy-treated mice had similar striatal lesions, excluding that LID improvement by Doxy could result from neurorestorative effects. Importantly, LID inhibition by Doxy was associated with decreased Fos-B and COX-2 expression and reduced levels of PGE2, TNF-α, and IL-1β in the dorsolateral striatum of dyskinetic mice. We conclude (i) that Doxy has the potential to prevent LID regardless of the intensity of dopaminergic lesioning and (ii) that the anti-inflammatory effects of Doxy probably account for LID attenuation. Overall, the present results further indicate that Doxy might represent an attractive and alternative treatment for LID in PD.